Implementation of Direct Correction Technique in Improving Students’ Motivation towards Arabic Language Learning at MTs Muhammadiyah Pasui - Eran Batu, Anugrah; Mauludiyah, Lailatul; Murdiono, Murdiono (Kilmatuna: Journal Of Arabic Education, 2024)
Direct correction technique is part of the evaluation method that has an important role in improving language mastery, and has implications for increasing student motivation. This study aims to analyse whether Direct correction can increase students’ learning motivation in Arabic language learning with the object of research at Islamic Junior High School (MTs) Muhammadiyah Pasui. Then there are two problem formulations. First, what are the factors or obstacles that affect Arabic language learning at MTs Muhammadiyah Pasui. Second, how Direct correction increases the motivation of learning Arabic vocabulary of MTs Muhammadiyah Pasui students’. To answer the research problem, this research uses a descriptive Quantitative method with data collection methods using interviews and questionnaires. The analysis technique uses validity test and reliability test. This study concluded that first, students’ obstacles in learning are influenced by the lack of mufradat vocabulary and the majority of students’ have difficulty in reading the Qur'an, which has an impact on their inability to identify letters. Second, students’ lack of interest is influenced by students’ low level of understanding of the material, with the application of Direct correction teachers can measure students’ level of understanding and students’ can immediately correct mistakes after evaluation activities. Third, with the application of Direct correction the teacher is able to foster student learning motivation, the indicators are that students’ are active in learning, students’ pay more attention to learning, students’ become more excited and feel facilitated.